LEVERAGING USER-GENERATED CONTENT (UGC) IN ENHANCING OPEN AND DISTANCE LEARNING INSITUTION: A COMPREHENSIVE STUDY ON STUDENT FEEDBACK AND EVALUATION - Musa, Norfardilawati; Md Noor, Shuhaida; Mary Richard, Christina (Universitas Terbuka, 2024)
User-generated content (UGC) refers to any form of content created and shared by users or consumers through various online platforms and social media channels, rather than by the brand or organisation itself. The advent of the internet and social media platforms has greatly facilitated the generation and dissemination of user-generated content. UGC has become a powerful tool for consumers to engage with brands, influence others, and shape brand perceptions which directly or indirectly impact the image of the organisations. Unlike conversations or interactions initiated by brands or organisations, UGC offers more spontaneous, authentic and truthful feedback compared to other forms of feedback mechanism. While not all feedback or interactions may be positive, paying attention to UGC will allow brands or organisations to monitor the situation on the ground, address issues immediately, and strategize effectively for improvements. Open and distance learning (ODL) institution is one of the organisations that can be affected by UGC related to their products or services. With stiff competition among higher education providers, both public and private universities, ODL institutions play a crucial role in providing accessible and flexible educational opportunities for distance learners. To be on par with other established universities, ODL institutions must ensure continuous improvement and effectiveness of their ODL programmes. Therefore, these institutions need to gather and analyse the information shared regarding the products and services offered to them. This research aims to investigate the application of UGC in collecting, analysing and utilising student feedback to enhance the quality of open and distance learning programmes. The research will explore the utilisation of UGC in collecting student feedback and evaluations in an ODL institution to understand student experiences, engagement levels, interaction patterns, and content creation practices through the analysis of UGC. It will identify strengths and weaknesses revealed or shared in the UGC related to open and distance learning programmes offered and recommend ways for continuous enhancement of open and distance learning experiences based on the analysis of UGC. The research will apply mixed-methods, combining qualitative and quantitative techniques to gather and analyse data. In the first phase of the study, qualitative method will be employed to identify the collection of related UGC using Octoparse software to extract data related to the ODL institution from any public website. The data will be analysed thematically to gain insight into students’ experiences, challenges and preferences. In the second phase, a survey will investigate key variables that emerge from the first phase. The survey will focus on verifying issues raised by the students, factors influencing the OUM students’ perceptions of OUM services and products, their satisfaction, and their suggestions for improvements. This research is expected to provide valuable insights to improve program quality, meet the specific needs of distance learners, and foster a culture of continuous improvement. The research outcomes will contribute to advancing open and distance learning practices and enhancing the quality of educational experiences.